A study on submuscular bridge plating in paediatric femoral diaphyseal fracture - Asaduzzaman, Mohammad; Alam, Quazi Shahid-Ul; Musa, Mohammad; Rahman, Mohammad A.; Rabbi, Qaisur; Sobhan, Syed A. (International Journal of Research in Orthopaedics, 2025)
Background: Pediatric femoral diaphyseal fractures represent a significant orthopedic challenge, often resulting from falls or motor vehicle accidents. Conservative treatments like traction and spica casting suit younger children, but surgery is preferred for older children to reduce hospitalization and immobility. This study aimed to assess the efficacy and safety of submuscular bridge plating (SBP) as a treatment modality for pediatric femoral diaphyseal fractures. Methods: This prospective study was conducted at Sylhet MAG Osmani Medical College Hospital between February 2023 and February 2024, involving 40 patients aged 6–15 years. The study included closed fractures (AO 32A123) and excluded open fractures, pathological fractures, supracondylar extensions, and infections. A minimally invasive technique with dynamic compression plates was used, with follow-ups at 6 weeks and 3 months. Results: The study cohort had an average age of 10.4 years, with a male predominance (75%). Injuries were primarily caused by falls (60%) and road traffic accidents (30%). Fracture patterns ranged from oblique (40%) to comminuted (15%), with most located in the middle third of the femoral shaft. Postoperative complications occurred in 25% of cases, including superficial wound infections (15%) and deep infections requiring intervention (10%). Callus formation was observed at an average of 7.2 weeks, with minimal limb length discrepancies (mean: 1.2 cm). Functional outcomes, assessed using the Flynn score, were excellent in 85% of cases. Conclusions: Submuscular bridge plating demonstrates a reliable and effective solution for managing pediatric femoral diaphyseal fractures, offering excellent functional outcomes and low complication rates.